Studi Mineralogi Batuan Basal Sebagai Source-rock Bijih Besi Daerah Bontocani Kabupaten Bone, Sulawesi Selatan - Hasbi Bakri; Anshariah Anshariah; Firdaus F; Arif Nurwaskito; Alam Budiman Thamsi; Habibie Anwar; Emi Prasetyawati Umar (Universitas Muslim Indonesia, 2022)
Research has been carried out regarding the source rock of iron ore deposits. This area became the object of research because of the discovery of iron ore deposits and several other metals. In this research, the focus of the study is the source rock that carries Fe metal. The results of the initial study indicate that the basalt is thought to have carried the metal intruding the wall rock causing a reaction to occur. The analysis in this paper consists of field research, sampling, preparation, and analysis of petrography and XRD. Based on petrographic observations, basalt is composed of the main minerals in the form of pyroxene minerals, plagioclase, and base mass with a distinctive texture in the form of a porphyry texture where pyroxene and plagioclase minerals as phenocrysts are embedded in the base mass and opaque minerals. The secondary minerals found were epidote, actinolite, hornblende, anatase, staurolite, carbonate minerals, chlorite, sericite, magnesite, clay minerals, and quartz. The ore minerals are magnetite, goethite, chamosite, and pyrope.